"Wawacan Nata Sukma": Tracing the traces of classical Sundanese literature from the dark history of colonialism to the identity politics of oppressed nations from a performing arts perspective - Rusmana, Tatang; Ahadiat, Endut (Technium Social Sciences Journal, 2024)
Reading about the Sundanese people of Bandung Regency after the 17th century, one can learn from the Wawacan literary works, which helped shape the collective minds of the people. Wawacan is strongly influenced by Islamic teachings, which are depicted in sagas in the form of poetry called dangding (poetic bond). This research examines Wawacan Nata Sukma, written anonymously by the people of Banjaran on the slopes of Mount Cupu Pangalengan in Bandung Regency. Writing using Pegon (Arabic) letters, Sundanese language, 1833 AD (18th century) during the "forced cultivation" period of growing coffee under Dutch colonialism. The story Wawacan Nata Sukma contains the metaphorical, wild, intriguing, and patriotic resistance of the character "Nata Sukma". Staged from 1930 to 1960 in Bandung Regency. Nata Sukma struggled beyond war and oppression. He succeeded in deepening knowledge, changing fate, and achieving a dignified life after defeating the kings of five countries. Wawacan Nata Sukma is a reportage and portrait of events that occurred during the "forced cultivation" period and is related to the politics of the national identity of the oppressed. Research uses a hermeneutic perspective and qualitative methods in describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually and in groups.